2015
DOI: 10.17155/spd.75424
|View full text |Cite
|
Sign up to set email alerts
|

Formasyon Eği̇ti̇mi̇ Alan Bi̇reyleri̇n Alçakgönüllülük Düzeyleri̇ni̇n Farkli Deği̇şkenlere Göre İncelenmesi̇

Abstract: Elde edilen sonuçlar, katı lımcıların alçak gönüllülük düzeylerinin cinsiyet açısından kadınlar, bölüm değişkeni açısından ise rekreasyon mezunları lehine istati sti ksel olarak farklılaştı ğını ortaya koymaktadır. Yaş ve gelir düzeyi değişkeni açısından ise anlamlı bir farklılaşma gözlenmemişti r. Diğer yandan aile tutum değişkenine göre kendinden vazgeçme alt boyutunda ve toplam alçak gönüllülük boyutunda gruplar arasında anlamlı farklılık tespit edilmişti r. Bu farklılık "kendinden vazgeçme" alt boyutunda i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Gediksiz (2013) also found that the total score of humility did not change according to the income level in his master's thesis. Türkçapar and Karademir (2016) also found that neither humility total score nor its subdimensions differed significantly according to family income level. The findings are similar to the current results.…”
Section: Discussion and Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Gediksiz (2013) also found that the total score of humility did not change according to the income level in his master's thesis. Türkçapar and Karademir (2016) also found that neither humility total score nor its subdimensions differed significantly according to family income level. The findings are similar to the current results.…”
Section: Discussion and Resultsmentioning
confidence: 69%
“…However, in another study, a significant difference was found in the self-assessment sub-dimension of university students in favor of male and in favor of female in the sub-dimensions of focus on others, but it was reported that general humility did not differ significantly according to gender (Karademir, 2019). Türkçapar and Karademir (2016) indicated that the sub-dimensions did not differ significantly by gender, but that the total score of humility was significantly higher than that of females. The majority of the studies examined were not interested in the sub-dimensions that were processed with the total score of humility.…”
Section: Discussion and Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Öğrenimleri sırasında daha az maddi imkânlar dâhilinde geçinmeye çalışan öğrencilerin daha alçakgönüllü oldukları görülmektedir. Türkçapar ve Karademir (2016), Gediksiz (2013) ve Shıkholeslamı (2016)'ın çalışmalarında da gelir düzeyleri farklı olan öğrencilerin alçakgönüllülük puanlarında gruplar arasında fark tespit edilememiştir. Bu araştırmanın sonuçları da literatür çalışması sonuçları ile benzerlik göstermektedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified